INVESTIGATING MUHAMMADIYAH UNIVERSITY EFL LEARNERS’ GRAMMAR ERRORS IN WRITING DESCRIPTIVE PARAGRAPHS - A MAPPEWALI N (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
This writing aims at investigating Muhammadiyah University EFL learners’ grammar errors in writing descriptive paragraphs and the causes of the errors. This employed a qualitative research in descriptive design by using error analysis. investigating four aspects of grammar errors including addition, omission, misformation and misordering which is called surface strategy taxonomy, they thenwere analyzed by employing grammar units of analysis. These units were applied to identify errors of sentence elements. From the investigation, it is found that EFL learners’ tendency of making grammar errors in writing descriptive paragraphs was sourced from Bahasa Indonesia interference. They adopted a set of rule in Bahasa Indonesia into target language. Key Terms: Errors, Descriptive paragraphs, and Surface strategy taxonomy.